Future directions in distance learning and communication technologies - Shih, Timothy K. 1961-.; Hung, Jason C. 1973-.; Gale Group (Hershey, Penn. Idea Group Pub., 2007)
This book summarizes theoretical studies and practical solutions for engineers, educational professionals, and graduate students in the research areas of e-learning, distance education, and instructional designs. Readers will find solutions and research directions in this interesting book.
Electronic reproduction.
Keywords: Instructional systems -- Design; Distance education; Multimedia systems; Teaching -- Aids and devices; Educational technology; Electronic books